Immediate versus delayed implant placement in the esthetic zone: a prospective 3D volumetric assessment of peri-implant tissue stability - Puria Parvini; Katharina Melissa Müller; Emilio A. Cafferata; Frank Schwarz; Karina Obreja (SpringerOpen, 2022)
Abstract Purpose To evaluate the volumetric stability of peri-implant soft and hard tissue prospectively, this study compared immediate versus delayed implants placed in the anterior esthetic region. Methods This non-randomized controlled clinical study included 25 patients, who received an immediate (type 1) or a delayed (type 4) implant placement for the replacement of a single anterior tooth. The anterior maxillae were intraorally scanned at three timepoints: before surgery (S0), 6 months (S1), and 12 months (S2) after surgery. A specific region of interest (ROI), divided into marginal and apical regions, was determined and superimposed for volumetric changes analysis. At 6 and 12 months, the probing depth (PD), bleeding/suppuration on probing (BOP/SUP), modified plaque index (PI), keratinized mucosa (KM) width, mucosal recession (MR), and implant stability (PTV) by means of periotest were recorded. Results Between S0-S2, tissue surrounding immediate implants was reduced in 0.37 ± 0.31 mm, whereas delayed implants gained 0.84 ± 0.57 mm mean tissue volume. Peri-implant tissue loss at type 1 implants occurred primarily in the marginal section of the ROI (0.42 ± 0.31 mm), whereas tissue gain at type 4 implants occurred mainly in the apical section (0.83 ± 0.51 mm). These values were significantly different between both groups for the entire ROI (p = 0.0452) and the marginal region (p = 0.0274). In addition, the mean buccal KM width around type 1 implants was significantly wider in comparison with the type 4 implants group after 12 months (p = 0.046). There were no significant differences between groups regarding PD, BOP/SUP, or PTV. Conclusions The results suggest that type 1 implants placed in the esthetic region experience more tissue loss than type 4 implants, thus marginal tissue remodeling should be considered for planning immediate implants placement in the anterior maxillae. Graphical Abstract